Nipple-Areolar Complex Reconstruction: A Review of the Literature and Introduction of the Rectangle-to-Cube Nipple Flap - Henderson, Joshua T. (Eplasty, 2018)
Objective: There are many approaches to nipple-areola complex reconstruction. Tissue quality and thickness, desired nipple location and size, scar position, and surgeon preference all play a role in selecting a technique. We present the rectangle-to-cube nipple flap, a new technique for challenging nipple reconstruction. A review of published techniques is compared and contrasted with this flap design. Methods: Following bilateral total skin-sparing mastectomies, a patient with breast cancer underwent breast reconstruction with tissue expanders and subsequent nipple reconstruction with the rectangle-to-cube nipple flap. An inferiorly based rectangular flap with medial and lateral extensions is designed inferior to the transverse scar. Upon elevation and rotation, the medial and lateral flaps form a cube. Results: In all cases of rectangle-to-cube nipple flaps performed at our institution, adequate nipple projection and patient satisfaction have been achieved at 2-month postoperative evaluation. Conclusion: The rectangle-to-cube nipple flap provides sustained nipple projection due to the de-epithelialized base on which the flap sits. The rectangle-to-cube nipple flap also takes advantage of a long transverse scar, and it can be extended to include longer scars for scar revisions.